If there be thorns [videorecording (DVD)] - Lewis, Jason, 1971-; Graham, Heather, 1970-; Carpani, Rachael, 1980-; Andrews, V. C. (Virginia C.) ([Publisher not identified], 2015)
The third installment in the Flowers in the Attic series follows the tragically dysfunctional Dollanganger family as they try to escape their past, only to find out there are some things that you can never get away from.